Pengaruh Fasilitas Kamar dan Perceived Value pada Minat Beli di Hotel - Irfan, Muhammad; Utami, Nisa Rahmaniyah (Stupa, 2022)
The purpose of this study is to determine the dominant factor of room facilities in negative reviews and to determine consumer buying interest at the Horison Ultima hotel. This study uses a quantitative descriptive research method, which uses an application that is calculated using the T test. The sample in this study was taken by random sampling and involved 100 respondents. The results showed that all variables received good ratings by the respondents. Multiple Regression Test shows that Room Facilities and Perceived Value variables have a significant simultaneous (together) effect on Purchase Interest at Horison Ultima Hotel Bekasi.